2014
DOI: 10.1002/pds.3638
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Guillain–Barré syndrome following pandemic influenza A(H1N1) 2009 vaccination in Germany

Abstract: PurposeA prospective, epidemiologic study was conducted to assess whether the 2009 pandemic influenza A(H1N1) vaccination in Germany almost exclusively using an AS03-adjuvanted vaccine (Pandemrix) impacts the risk of Guillain–Barré syndrome (GBS) and its variant Fisher syndrome (FS).MethodsPotential cases of GBS/FS were reported by 351 participating hospitals throughout Germany. The self-controlled case series methodology was applied to all GBS/FS cases fulfilling the Brighton Collaboration (BC) case definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
(55 reference statements)
4
19
0
1
Order By: Relevance
“…However, other studies reported increased rates of GBS during pandemic periods [5,7]. Indeed, a few studies have even found a small but significant increase in the GBS incidence rate after pH1N1 vaccination [8][9][10][11]28,29]. Vaccination for pH1N1 appears to be accompanied by 0.74-2 additional GBS cases per million doses, which are similar to studies of the seasonal influenza vaccine [8,11,30].…”
Section: Discussionsupporting
confidence: 57%
“…However, other studies reported increased rates of GBS during pandemic periods [5,7]. Indeed, a few studies have even found a small but significant increase in the GBS incidence rate after pH1N1 vaccination [8][9][10][11]28,29]. Vaccination for pH1N1 appears to be accompanied by 0.74-2 additional GBS cases per million doses, which are similar to studies of the seasonal influenza vaccine [8,11,30].…”
Section: Discussionsupporting
confidence: 57%
“…A Canadian study showed a small but significant increase in the number of GBS cases after mass influenza vaccination in Quebec [21] and a study from Germany on the Pandemrix vaccine reported a statistically significant association between GBS and vaccination in a 5-42 days risk window [6]. Unlike other studies, an American study by Vellozzi et al [22] suggested a protective effect of influenza A (H1N1) vaccination.…”
Section: Comparison To the Literaturementioning
confidence: 60%
“…While some studies show a lack of association between GBS following influenza A (H1N1) vaccination [3,8,9,14,20], an increased risk of GBS following pandemic vaccination has been reported in other studies [5,6,21,22]. Many of these studies, however, did not address influenza infection as a risk factor for GBS.…”
Section: Comparison To the Literaturementioning
confidence: 79%
See 2 more Smart Citations